Porous plga sheet and acellularized muscle stuffed vein seeded with neural- differentiated mscs are potential scaffolds for nerve regeneration - NH, Hidayah; Sulong, Ahmad Fadzli; Ng, MH; AS, Naicker; A, Shalimar (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2012)
Numerous studies on bridging a nerve gap without using autologous nerve graft have been reported. Our study compares two models of nerve conduit; a porous PLGA sheet and acellular muscle stuffed vein with both models seeded with mesenchymal stem cells. The micro-porous PLGA sheet was fabricated by solvent casting/salt leaching technique using methylene chloride as the solvent. Both PLGA and muscle stuffed vein was decellularized by liquid nitrogen immersion and the latter further hydrolyzed by soaking in HCl for 24 hours. Neural-differentiated mesenchymal stem cells (MSCs) were seeded and cultured on the surface of both conduits. We studied the seeded constructs for their surface morphology by scanning electron microscope and biocompatibility assessment. Both models of nerve conduit had good distribution and proliferation of seeded cells. For the PLGA sheet, pores had extensive interconnections, excellent for allowing nerve growth. For the muscle stuffed vein, cells were successfully embedded within the hydrolyzed fraction of muscle and ultra structural analysis showed healthy cells attached to the surface of a cellular muscle. In conclusion, both PLGA and muscle stuffed vein seeded with neural-differentiated MSCs are suitable scaffolds for nerve tissue engineering